Pendampingan Evaluasi Kesesuaian Laporan Keuangan Dengan PSAK No. 16 Pada CV. Jagor Jaya - Natalia, Natalia; Iriyadi, Iriyadi; Setiawan, Hendra (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
CV. Jagor Jaya is an industrial company that produces folding gates, harmonica doors and various types of products related to building materials equipment such as PVC pipes, hoses and other door accessories. This results in fixed assets being one of the supporting factors that have an important role in supporting the company's operational activities. As a result, if there is a discrepancy in the accounting treatment, it can result in quite material misstatements. This assistance aims to compare the suitability of the accounting treatment for the company's fixed assets and their presentation in CV's financial reports. Jagor Jaya is based on PSAK 16. The mentoring method used is descriptive qualitative by describing problem identification in detail and systematically by comparing the results of field research, namely in the form of accounting policies in each company's financial report with generally accepted accounting policies, namely Statement of Financial Accounting Standards No. 16. Data collection procedures were carried out by means of observation, interviews, documentation and literature study. The results of the assistance show that CV's accounting treatment. Jagor Jaya is not yet fully compliant, there is a mismatch in CV's accounting treatment. Jagor Jaya based on PSAK 16 such as errors in the recognition of expenses which resulted in errors in presenting the acquisition value and depreciation expenses of fixed assets in the statement of financial position and profit and loss statement and several costs that were not included in the measurement of assets and fixed assets whose useful life had expired but remained used by the company in the company's daily activities. The company does not recognize office inventory with a useful life of more than one year as fixed assets. The depreciation method used by the company is the straight line method. In 2018, there were no additions or reductions in assets. Regarding disclosure, the company has not implemented detailed reporting regarding fixed assets in the notes to the financial statements. However, based on the confirmation results, the company adheres to principle-based which relies more on management principles and judgment. Keywords: Fixed Assets, Accounting Treatment of Fixed Assets, Conformity of Accounting Treatment with PSAK 16